Fractional Flow Reserve–Guided Complete Revascularization Improves the Prognosis in Patients With ST-Segment–Elevation Myocardial Infarction and Severe Nonculprit Disease: A DANAMI 3-PRIMULTI Substudy (Primary PCI in Patients With ST-Elevation Myocardial Infarction and Multivessel Disease. (April 2017) - Lønborg, Jacob; Engstrøm, Thomas; Kelbæk, Henning; Helqvist, Steffen; Kløvgaard, Lene; Holmvang, Lene; Pedersen, Frants; Jørgensen, Erik; Saunamäki, Kari; Clemmensen, Peter; De Backer, Ole; Ravkilde, Jan; et al.
Abstract : Background—: The impact of disease severity on the outcome after complete revascularization in patients with ST-segment–elevation myocardial infarction and multivessel disease is uncertain. The objective of this post hoc study was to evaluate the impact of number of diseased vessel, lesion location, and severity of the noninfarct-related stenosis on the effect of fractional flow reserve–guided complete revascularization. Methods and Results—: In the DANAMI-3-PRIMULTI study (Primary PCI in Patients With ST-Elevation Myocardial Infarction and Multivessel Disease: Treatment of Culprit Lesion Only or Complete Revascularization), we randomized 627 ST-segment–elevation myocardial infarction patients to fractional flow reserve–guided complete revascularization or infarct-related percutaneous coronary intervention only. In patients with 3-vessel disease, fractional flow reserve–guided complete revascularization reduced the primary end point (all-cause mortality, reinfarction, and ischemia-driven revascularization; hazard ratio [HR], 0.33; 95% confidence interval [CI], 0.17–0.64; P =0.001), with no significant effect in patients with 2-vessel disease (HR, 0.77; 95% CI, 0.47–1.26; P =0.29; P for interaction =0.046). A similar effect was observed in patients with diameter stenosis ≥90% of noninfarct-related arteries (HR, 0.32; 95% CI, 0.18–0.62; P =0.001), but not in patients with less severe lesions (HR, 0.72; 95% CI, 0.44–1.19; P =0.21; P for interaction =0.06). The effect was most pronounced in patients with 3-vessel disease and noninfarct-related stenoses ≥90%, and in this subgroup, there was a nonsignificant reduction in the end point of mortality and reinfarction (HR, 0.32; 95% CI, 0.08–1.32; P =0.09). Proximal versus distal location did not influence the benefit from complete revascularization. Conclusions—: The benefit from fractional flow reserve–guided complete revascularization in ST-segment–elevation myocardial infarction patients with multivessel disease was dependent on the presence of 3-vessel disease and noninfarct diameter stenosis ≥90% and was particularly pronounced in patients with both of these angiographic characteristics. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01960933. Abstract : Supplemental Digital Content is available in the text.